Behavioral Interventions for Pediatric Food Refusal Maintain Effectiveness Despite Integrity Degradation: A Preliminary Demonstration. Issue 5 (September 2020) - Ulloa, Gabriella; Borrero, Carrie S. W.; Borrero, John C.
Food refusal is commonly treated using behavioral treatment packages consisting of differential reinforcement of alternative behavior (DRA) and escape extinction. However, the effectiveness of such behavioral interventions is inextricably linked to the integrity with which the procedures are conducted. Although previous research has evaluated the effects of treatment integrity failures for behavioral interventions related to severe problem behavior and academic skill acquisition, the effects of these failures in the area of pediatric food refusal remain unknown. We conducted a parametric analysis to assess the effects of varying levels of errors on the treatment efficacy of contingent tangibles and attention, and escape extinction. Once stable responding was observed during an initial evaluation of treatment, participants were exposed to sessions of reduced-integrity treatment in descending order (i.e., 80%, 60%, 40%, and 20%) and subsequently exposed to full-integrity treatment (100% integrity). For one participant, integrity errors became detrimental to treatment when the level of integrity was decreased to 40%. For the other two participants, contingent tangibles and attention, and escape extinction remained effective despite being implemented with low integrity. Our preliminary demonstration suggests that behavioral interventions for pediatric food refusal remain effective despite considerable treatment integrity degradation.